Antibiotic consumption is a major driver of antibiotic resistance in calves raised on Italian cow-calf beef farms. (July 2022) - Ferroni, L.; Albini, E.; Lovito, C.; Blasi, F.; Maresca, C.; Massacci, F.R.; Orsini, S.; Tofani, S.; Pezzotti, G.; Diaz Vicuna, E.; Forte, C.; Magistrali, C.F.
Abstract: Although its importance, little information is available on antibiotic-resistance in cow-calf beef farms. This study aimed to determine prevalence and risk factors for antibiotic-resistant organisms in this livestock system. Fifty-four farms from Central Italy were included to assess the presence of antibiotic-resistant indicator Escherichia coli and of ESBL and/or AmpC-producing E. coli (ESBL/AmpC-EC) in calves. Antimicrobial usage (AMU) was recorded, and farm-related variables were collected through questionnaires. Potential risk factors were tested using a mixed-effects logistic regression model. The presence of resistant- E. coli was recorded in 75.9% of farms (95% confidence interval [CI]: 62.4–86.5) with resistance to tetracyclines, sulfonamides, penicillins, and fluoroquinolones as the most frequent. The prevalence of farms positive for ESBL/AmpC-EC was 35.2% (95% CI: 22.7–49.4). AMU on the farms originating a resistant- E. coli was higher than that on the farms originating a susceptible- E. coli . The same difference was found for the consumption of beta-lactams (beta-DCD/year) and AMU via the parenteral route, which resulted also associated with the presence of ESBL/AmpC-EC. Farms with higher beta-DCD/year had an increased risk of being positive for resistant- E. coli, whereas farms with higher overall AMU had an increased risk for ESBL/AmpC-EC presence. Among farm-related factors, only farm size was associated with the presence of ESBL/AmpC-EC (odds ratio: 5.8, 95% CI: 1.3–26.3). Our findings highlight a reduction of the risk of ESBL/AmpC-EC in small cow-calf farms, and a strong association between AMU and antibiotic-resistance. Antibiotic stewardship programs are needed to improve the health status of cow-calf farms and ensure their long-term sustainability. Highlights: Overall, 79% of cow-calf beef farms had at least one AR indicator E. coli in calves. Multi-resistant isolates were found in 50% of farms. Farms with high beta-lactam consumption were at increased risk of AR E. coli. Farms with high antibiotic consumption were at risk of ESBL/AmpC-producing E. coli. A large farm size was associated with ESBL-/AmpC-producing E. coli.